Do Forgiveness Campaign Activities Improve Forgiveness, Mental Health, and Flourishing? - Andrea Ortega Bechara; Zhuo Job Chen; Richard G. Cowden; Everett L. Worthington; Loren Toussaint; Nicole Rodriguez; Hernan Guzman Murillo; Man Yee Ho; Maya B. Mathur; Tyler J. VanderWeele (Frontiers Media S.A., 2024)
Objectives: To evaluate the effectiveness of a forgiveness public health intervention at promoting forgiveness, mental health, and flourishing.Methods: Colombian students (N = 2,878) at a private, nonreligious university were exposed to a 4-week forgiveness community campaign and were assessed pre- and post-campaign.Results: Forgiveness, mental health, and flourishing outcomes showed improvements after the campaign. On average, participants reported engaging in 7.18 (SD = 3.99) of the 16 types of campaign activities. The number of types of campaign activities that participants engaged in evidenced a positive linear association with forgiveness, although some activities were more popular than others and some activities were more strongly associated with increased forgiveness. For depression, anxiety, and flourishing, engaging in more activities was generally associated with greater improvements, but the patterns were less consistent relative to forgiveness.Conclusion: This forgiveness public health intervention effectively promoted forgiveness, mental health, and flourishing. Effective campaigns in diverse communities involve promoting mental and physical health through forgiveness. However, recent conflict may hinder acceptance, necessitating political capital for leadership advocating forgiveness initiatives.